SIRT1 Signaling Is Involved in the Vascular Improvement Induced by Moringa Oleifera Seeds during Aging - Valeria Conti; Joseph Iharinjaka Randriamboavonjy; Herintsoa Rafatro; Valentina Manzo; Jessica Dal Col; Amelia Filippelli; Graziamaria Corbi; Angela Tesse (MDPI AG, 2023)
Vascular aging is linked to reduce NO bioavailability, endothelial dysfunction, oxidative stress, and inflammation. We previously showed that a 4-week treatment of middle-aged Wistar rats (MAWRs, 46 weeks old) with Moringa oleifera seed powder (MOI, 750 mg/kg/day) improved vascular function. Here, we investigated the involvement of SIRT1 in MOI-induced vascular improvement. MAWRs were treated with a standard or MOI-containing diet. Young rats (YWR, 16 weeks old) were the controls and received a standard diet. The hearts and aortas were harvested to evaluate SIRT1 and FOXO1 expression via Western blot and/or immunostaining, SIRT1 activity via a fluorometric assay, and oxidative stress using the DHE fluorescent probe. In the hearts and aortas, SIRT1 expression, reduced in MAWRs compared to YWRs, was enhanced in MOI MAWRs. In the hearts, SIRT1 activity did not differ between YWRs and MAWRs, whereas it was increased in MOI MAWRs compared with them. In the aortas, SIRT1 activity decreased in MAWRs, and it was similar in the MOI MAWRs and YWRs. FOXO1 expression increased in the nuclei of MAWR aortas compared to YWR and was reversed in MOI MAWRs. Interestingly, MOI treatment normalized oxidative stress enhanced in MAWRs, in both the heart and aorta. These results demonstrate the protective role of MOI against cardiovascular dysfunction due to aging via enhanced SIRT1 function and subsequently reduced oxidative stress.